IYEQ AS A DOMINANT SIGNIFIER OF POLITENESS IN THE SIDRAP BUGIS LANGUAGE OF SOUTH SULAWESI: A SOCIOPRAGMATIC PERSPECTIVE - Rijal, Syamsul; Nurjannah, Sitti; Mursidin, Muthmainnah (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Iyeq as a Dominant Politeness Marker in Sidrap Buginese in Sulawesi Selatan: A Sociopragmatic Perspective". The Buginese language in South Sulawesi has several dialects, one of which is the Sidenreng Rappang (Sidrap) dialect. A distinguishing feature of the Sidrap dialect is the high and rapid intonation of its speakers. Due to this intonation, the Sidrap dialect is sometimes perceived as harsh by speakers of other Buginese dialects. However, language cannot be judged solely on speed and intonation, as numerous underlying social factors influence it, including differing standards and markers of politeness. This article is based on a study conducted in Macorawalie Village, Panca Rijang District, Sidrap Regency. The findings reveal that, in addition to age and occupation, speakers of the Sidrap dialect also take family or kinship relations into account when selecting language varieties in conversation. For instance, among older adults, the honorific variety is still employed even when interlocutors are close and of the same age. Furthermore, the word iyeq is identified as a dominant politeness marker in Sidrap Buginese speech. The word iyeq functions as an honorific complement within the politeness strategies of the Sidrap Buginese community. In conversational contexts, the word iyeq is consistently found and is generally placed at the beginning of a sentence.